Aspergillosis of thyroid gland managed by thyroidectomy. Issue 4 (18th October 2013) - Dag, Ahmet; Akca, Tamer; Ersoz, Gulden; Cinel, Leyla
<x xml:space="preserve">Abstract</x> We experienced a very rare case of thyroidal Aspergillus in a 65‐year‐old man who came to our hospital complaining of fever and persistent pain in the articulations. The patient had a history of chronic renal failure. After physical examination and imaging tests, fine‐needle biopsy of the thyroid showed fungus hyphae angling at a45‐degree compatibility with Aspergillus and thyrocites, with Hurthle cell differentiation. We performed left thyroidectomy without any complications. Because most of thyroidal Aspergillus diagnoses are made after autopsy and insufficient data about its management, we present, to the best of our knowledge, the first case of thyroidal Aspergillus in the literature that was treated by left thyroidectomy successfully.